Hubungan Konsumsi Makanan Kariogenik, Kebiasaan Menggosok Gigi Dan Peran Orang Tua dengan Karies Gigi Pada Anak KelaS III - damayanti, yossi fitria; Sabaruddin, Erny Elviany; Hafidah, Nasya (JURNAL KESEHATAN TERAPAN, 2023)
Dental caries in childhood can affect a child's quality of life, because it can result in painful teeth, hampered nutritional intake and if not treated can hinder the child's growth resulting in missed school time due to toothache. The aim of this research was to determine the relationship between cariogenic food consumption, tooth brushing habits and the role of parents with dental caries in grade III children at SDN Pondok Ranggon 04 Pagi, using a cross sectional design with a quantitative approach. The data used is primary data, obtained using questionnaires and dental examinations to obtain data from a sample of all class III children totaling 118 respondents. The results of the study showed that 85 children (72%) had dental caries and there was a relationship between consumption of cariogenic foods (p = 0.001), tooth brushing habits (p = 0.005) and the role of parents (p = 0.002) with dental caries in third grade children. at SDN Pondok Ranggon 04 AM. It is hoped that the school can carry out a community movement related to dental health by forming "Dental Caries Ambassadors" as a driving force for all students to be independent in maintaining health and preventing dental caries